(untitled) (Third Sector Social Economic Review, 2023)
In this study, which was carried out in the health sector in Ankara, it was basically aimed to determine the relationships between visionary leadership, organizational commitment, career satisfaction and speaking behavior. Visionary Leadership Scale developed by Sashkin (1996) and consisting of 25 statements; Organizational Commitment Scale consisting of 18 statements, developed by Meyer, Allen and Smith (1993) and adapted into Turkish by Wasti (2000); Greenhaus et al. (1990) Career Satisfaction Scale consisting of 5 statements and the Voice Behavior Scale developed by Van Dyne and LePine (1998) consisting of 6 statements were used. The data were collected from 387 health workers working in main hospital of a foundation university in October-November 2022 by hand and e-mail. First of all, validity and reliability analyzes were made, and then, as a result of correlation analysis that there is a positive significant relationship between all variables. As a result of regression analysis, visionary leadership and organizational commitment have a significant effect on career satisfaction, and voice behavior. The findings obtained as a result of hierarchical regression show that organizational commitment has a partial mediation effect on the effect of visionary leadership on career satisfaction and expressing behavior in the examined hospital.